Assessing cognitive and executive function in childhood absence epilepsy - Salama, Samy; Saadallah, Horeya; Hamed, Mervat; El Wafa, Heba Abou; lhab Reda, M. (Progress in neurology and psychiatry (Guildford), 2023)
Although cognitive impairment is one of the common problems among many patients with epilepsy, it is still not well defined in childhood absence epilepsy. Here, the authors assess the cognitive and executive function in childhood absence epilepsy in a group of school‐age children in Egypt. They discuss the need for early identification of neuropsychological dysfunction so that appropriate management can be implemented.